1996
DOI: 10.1002/(sici)1097-0223(199610)16:10<893::aid-pd962>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Molecular Genetic Characterization of Trisomy 20 Mosaicism in Fetal Blood and Tissues

Abstract: We report a case of mosaic trisomy 20, the most common autosomal mosaicism identified in amniocytes, ascertained in a woman referred for amniocentesis because of abnormal ultrasound at 18·1 weeks' gestation which revealed short femurs and nuchal thickening. Metaphase analysis of 98 clones revealed 47,XY,+20 in 96 cells (98 per cent). Trisomy 20 was demonstrated in 6 cells (12 per cent) in a total of 50 cells from two fetal blood cultures obtained after pregnancy termination. Fluorescence in situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…8 In that case, 10 dinucleotide repeat polymorphisms spaced along the short and long arms of chromosome 20 failed to reveal three different alleles in the proband DNA, and as no recombination was observed between markers, the findings suggested that the nondisjunction event most likely occurred postzygotically. 8 Biparental inheritance was detected in the diploid chorionic villi.…”
Section: Trisomy 20 Mosaicism and Upd20mentioning
confidence: 93%
See 3 more Smart Citations
“…8 In that case, 10 dinucleotide repeat polymorphisms spaced along the short and long arms of chromosome 20 failed to reveal three different alleles in the proband DNA, and as no recombination was observed between markers, the findings suggested that the nondisjunction event most likely occurred postzygotically. 8 Biparental inheritance was detected in the diploid chorionic villi.…”
Section: Trisomy 20 Mosaicism and Upd20mentioning
confidence: 93%
“…8 In that case, 10 dinucleotide repeat polymorphisms spaced along the short and long arms of chromosome 20 failed to reveal three different alleles in the proband DNA, and as no recombination was observed between markers, the findings suggested that the nondisjunction event most likely occurred postzygotically. 8 Biparental inheritance was detected in the diploid chorionic villi. 8 The fact that 78% of the reported prenatal cases of trisomy 20 mosaicism were diagnosed after an amniocentesis because of advanced maternal age, however, suggests a maternal age effect (and maternal meiotic origin in the majority of cases) as seen in other trisomies, ie 13, 16, 18, 21, and X.…”
Section: Trisomy 20 Mosaicism and Upd20mentioning
confidence: 93%
See 2 more Smart Citations